2022
DOI: 10.1186/s12888-022-03707-7
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress in iranian midwives: stimuli factors, outcomes and risk management

Abstract: Background The present qualitative study was conducted to explain the experiences of secondary traumatic stress (STS) and its related factors in midwives working in maternity wards. Methods Data were collected using semi-structured interviews with 11 midwives working in the maternity wards of hospitals in Urmia, Iran, through in-depth interviews with open-ended questions. Data were analyzed using the conventional content analysis approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Sohrabzadeh et al reported some of the reasons for not reporting violence, such as the belief in the futility of reporting, repetition of more than one case of violence, not having enough time to follow up, forgetting due to busy work, and considering the matter unimportant [54]. In a qualitative study of STS among midwives in Iran, Hajiesmaello et al found that verbal harassment by doctors, department o cials, shift o cials, or even colleagues of midwives had caused severe psychological damage to midwives [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sohrabzadeh et al reported some of the reasons for not reporting violence, such as the belief in the futility of reporting, repetition of more than one case of violence, not having enough time to follow up, forgetting due to busy work, and considering the matter unimportant [54]. In a qualitative study of STS among midwives in Iran, Hajiesmaello et al found that verbal harassment by doctors, department o cials, shift o cials, or even colleagues of midwives had caused severe psychological damage to midwives [30].…”
Section: Discussionmentioning
confidence: 99%
“…Job stress can occur when employees face more work than they can handle, leading to inappropriate work environments, high workloads and pressure, and organizational factors such as policies, structures, and role ambiguity [45]. Midwives experience signi cant job stress due to the burden of caring for maternal and fetal/newborn health, limited functional independence, a high volume and variety of tasks, and role con icts in their work environment [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Urmia, a study on secondary traumatic stress disorder in Iranian midwives con rmed that high workload and pressure, insu cient time, and the need for speeding up task accomplishment maximally contributed to perceived occupational stress and explained high belongingness to the midwifery profession as an element resisting this occupational stress. It reported that factors such as organizational-governmental structure, unbalanced distribution of power, and weakness of supportive rules enfeebled midwives' professional roles and led to emotional fatigue and occupational burnout (59). Due to the workload associated with caring for pregnant mothers, HPMs expectedly experience limited functional independence, organizational bias, task diversity, role con ict, and occupational stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, delivery room as a special medical unit, maternal or foetal death, neonatal resuscitation, postpartum haemorrhage, and other traumatic workplace events have become major causes of job stress for midwives [18,19]. Traumatic stress in midwives usually refers to the psychological stress response to an adverse birth event directly experienced or witnessed in the workplace [20,21].…”
Section: Introductionmentioning
confidence: 99%